Twinning arrangements and service delivery in Zimbabwe’s local authorities: the case of Bulawayo City Council (BCC) and Ethekwini (South Africa), from 2010-2017 - Chikwati, Judith Moreen (Midlands State University, 2021)
Town twinning is a global trend and is becoming more popular in Africa with Local authorities forming alliances with other municipalities within the region and abroad. Twinning arrangements originated after the Second World War as one of the diplomatic techniques to bring about peace and reconciliation amongst states. Bulawayo City Council had its first twinning arrangement in 1986 with Aberdeen City Council (Scotland). Since then, it has managed to forge alliances with Ethekwini Municipality (Durban- South Africa), Polokwane Municipality, Francistown City Council (Botswana) and the City of Siping (China). The study sought to assess the nexus between the twinning arrangements and service delivery by taking a close and critical look at various thematic concerns such as the causes of poor service delivery in Bulawayo. The researcher also proffered recommendations on how best to deal with the factors militating against effective and efficient service delivery. The author looked at decentralisation and the impact this concept would have on the development of cities in Zimbabwe. The second objective of this research was to examine the factors which led to the twinning arrangement with Ethekwini Municipality and this led to the third goal, which is the assessment of whether or not the set targets were met. The author also looked at the legislative frameworks guiding the Twinning arrangements. The study triangulated both the qualitative and quantitative methodologies in gathering data on the topic. The target population included the staff members, the elected officials, former students on attachment, Business community and the residents of Bulawayo. Questionnaires were sent to various respondents, interviews were also conducted and the researcher also made use of Council documents and files. Thus, research findings show that BCC has benefitted more from the twinning arrangements it has with other cities with the Ethekwini-BCC cooperation being the most fruitful one of them all. The researcher then recommended that the BCC formulates a twinning arrangements standing committee which will greatly decrease travelling costs by delegating the Chairperson of the committee to run errands on Council’s behalf. Other recommendation included the inclusion of the citizens of Bulawayo in TA issues and to empower the majority by focusing more on the educational sector through exchange programs.